Performance and Return to Sport After Excision of the Fractured Hook of the Hamate in Professional Baseball Players. Issue 12 (October 2020) - Erickson, Brandon J.; Mcelheny, Kathryn; Chalmers, Peter N.; Carr, James B.; D'Angelo, John; Rowe, Dana; Poulis, George; Lourie, Gary M.; Carlson, Michelle
Background: A fracture of the hook of the hamate is a common injury affecting professional baseball players. The treatment for these fractures ranges from nonoperative immobilization to excision of the fragment. Purpose/Hypothesis: The purpose was to report the results of surgical treatment of hook of hamate fractures in professional baseball players and determine which factors are associated with return to sport (RTS) and time to RTS. The hypothesis was that there is a high rate of RTS in professional baseball players after surgical treatment of the hook of the hamate fracture with no significant decline in performance after RTS. Study Design: Descriptive epidemiology study. Methods: All professional baseball players who underwent excision of the hook of the hamate between 2010 and 2017 were included. Player characteristic and performance data (before and after surgery) were recorded. Performance metrics were then compared before and after surgery. Results: Overall, 261 players were included. Of total injuries, 96% were due to hitting, 86% occurred on the nondominant hitting side, and 89% were acute fractures (11% were nonunion cases). Most (95%) injuries occurred at the Minor League level and 96.2% of procedures were performed by hand fellowship–trained surgeons. Eight percent of players underwent concomitant procedures. The average tourniquet time was 31 ± 13 minutes. In total, 81% of players returned to sport at the same or higher level; 3% returned to sport at a lower level. The median time to RTS after surgery was 48 days (range, 16-246 days). The tourniquet time and number of days to RTS were significantly associated with one another ( P = .001; Spearman ρ = 0.290; N = 130). Player utilization significantly increased after surgery. While player efficiency, including batting average (BA), on-base percentage (OBP), and on-base plus slugging percentage (OPS), significantly decreased, these changes were numerically small (BA: 0.26 ± 0.04 preoperatively vs 0.25 ± 0.04 postoperatively; OBP: 0.34 ± 0.04 preoperatively vs 0.32 ± 0.04 postoperatively; OPS: 0.73 ± 0.12 preoperatively vs 0.70 ± 0.11 postoperatively) ( P < .001). There were no significant differences between rates of RTS to the same or higher level of play among acute fractures (81%) and nonunion cases (76%) ( P = .837). Conclusion: After surgical excision for hook of hamate fractures in professional baseball players, 84% were able to RTS, with 81% returning to the same or higher level. The median time for players to RTS after surgery was 48 days. Player usage increased after surgery, while hitting efficiency slightly declined.